Enhanced sensing performance of ZnO nanostructures-based gas sensors: A review - Vijendra Singh Bhati; Mirabbos Hojamberdiev; Mahesh Kumar (Energy Reports, 2020)
Metal oxide semiconductors-based gas sensors have been extensively explored due to their high sensing response, cost-effectivity, long-term stability, and simple fabrication. However, their utilization at low operating temperature is still challenging. Thus, reduction in power consumption is highly essential for long-term usage of gas sensors. ZnO nanostructures-based gas sensors are one of the most eligible candidates where a real-time detection of explosive and toxic gases is needed. On this subject, numerous efforts have been made to improve the sensing response at reduced working temperature with the assistance of various methods. In this report, several techniques related to the synthesis of ZnO nanostructures and their efficient performance in sensing are reviewed. The report primarily focuses on different means of improving the sensing properties, such as functionalization of noble metal nanoparticles, doping of metals, inclusion of carbonaceous nanomaterials, using nanocomposites of different MO, UV activation, and post-treatment method of high-energy irradiation on ZnO nanostructures, with their possible sensing mechanisms. This study will therefore shed light on future proposals of ZnO-based gas sensors showing high sensitivity even at low operating temperature.
Keywords: 330; ZnO nanostructures; Gas sensors; Gas sensing mechanism; Nanocomposites; Carbonaceous nanomaterials